Preparation method of lithium ferric manganese phosphate positive electrode material with high compaction density

By adjusting the ball milling time and conditions, adjusting the particle size of the cathode material of iron manganese phosphate, and using spray drying and high-temperature sintering processes, the problem of low compaction density of the cathode material is solved, and the material performance and production efficiency are improved are achieved.

CN119581501APending Publication Date: 2025-03-07SINOSTEEL ANHUI TIANYUAN TECH +1

Patent Information

Application Number
CN202411687991.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, the preparation method of lithium-ion battery positive electrode material has an unstable ball milling process, resulting in uneven particles of the positive electrode material precursor and poor physical properties such as morphology, which in turn leads to a low compaction density of the positive electrode material, affecting electrochemical properties.

Method used

By adjusting the ball milling time and conditions, the particle size control of the ferromanganese lithium phosphate positive electrode material is achieved, and materials of different particle sizes are uniformly mixed. Spray drying and high-temperature sintering processes are used to prepare a ferromanganese lithium phosphate positive electrode material with particle size gradient distribution.

Benefits of technology

It improves the compaction density of the cathode material, improves the performance and production efficiency of the material, and simplifies the process steps, reduces costs, and is easy to be used in industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581501A_ABST
    Figure CN119581501A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium ferric manganese phosphate positive electrode material with high compaction density, and relates to the technical field of preparation of lithium ferric manganese phosphate positive electrode materials. The preparation method comprises the following steps: weighing raw materials, sequentially adding grinding balls and absolute ethyl alcohol according to a ball-to-material ratio, a large and small ball ratio and a solid-to-liquid ratio, and uniformly mixing; after the mixed materials are averagely divided into two groups, the two groups of mixed materials are subjected to continuous high-speed ball milling for different time, during the ball milling period, operation is suspended within a certain interval, and exhaust treatment is conducted; after the ball milling is finished, taking out a ball-milled material, and washing and sieving to obtain two groups of uniformly dispersed slurry; uniformly mixing the two groups of slurry, adding pure water according to a certain solid content, and then carrying out a spray drying process; after the spray drying process is completed, grinding the collected powder, putting the powder into a high-temperature tube furnace for high-temperature sintering, cooling and grinding to obtain the lithium ferric manganese phosphate positive electrode material; the method is simple in step, easy to implement, low in improvement cost and good in product compaction density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of lithium iron manganese phosphate positive electrode materials, and in particular to a method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density. Background Art

[0002] Positive electrode materials are key components of lithium-ion batteries, and their performance and price will have a great impact on lithium-ion batteries. Reasonable selection of positive electrode materials can significantly improve the capacity, cycle stability and rate performance of lithium-ion batteries, and promote the improvement of their energy density and power density, which will have a profound impact on the wider application of lithium-ion batteries. The positive electrode materials of lithium batteries that have been commercialized include lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate and ternary materials. Lithium iron manganese phosphate positive electrode material belongs to olivine structure, with a higher diffusion coefficient of lithium iron phosphate material and a higher working voltage of lithium manganese phosphate material. Lithium iron manganese phosphate has a relatively ideal market prospect due to its high conductivity, good stability and excellent cycle performance.

[0003] At present, the preparation methods of positive electrode materials for lithium-ion batteries mainly include solid-phase method, hydrothermal method, coprecipitation method, etc. Among them, the solid-phase method has the advantages of simple and convenient operation, low equipment cost, etc., and is widely used in industrial applications in the field of material production. Solid-phase ball milling is a commonly used synthesis method that can be used to prepare precursors of various materials. During the ball milling process, the powdered raw materials are mixed and reacted in a ball mill through the action of mechanical force to obtain the desired precursor powder. The solid-phase ball milling method has also been widely used in the preparation of positive electrode materials for lithium-ion batteries, specifically including the main processes such as raw material precursor preparation (mainly including ball milling, sintering and other processes) and high-temperature sintering.

[0004] The solid phase ball milling method has outstanding advantages in terms of economy and large-scale production, but there is also the problem of unstable ball milling process, which leads to uneven particles of positive electrode material precursors, poor physical properties such as morphology, resulting in low compaction density of positive electrode materials, which will eventually have a certain impact on the electrochemical properties of positive electrode materials for lithium-ion batteries. To this end, some researchers have proposed corresponding solutions. For example, in the invention patent application with the publication number CN116986574A and the name of a method for preparing a high compaction density lithium iron manganese phosphate, different raw materials and different sintering methods are used to prepare three kinds of lithium iron manganese phosphate materials with different particle sizes, and the three materials are mixed to prepare a high compaction density lithium iron manganese phosphate. However, the preparation process of this method is cumbersome, the process is complicated, the cost is relatively high, and the actual operation is time-consuming and labor-intensive, and the existing production steps are changed a lot, which is not conducive to production promotion; in addition, there are also schemes with complex equipment or the existing process flow needs to be changed, and the improvement cost is large, which is difficult to apply in practice. Therefore, there is an urgent need for a method for preparing a positive electrode material of lithium iron manganese phosphate with a high compaction density to solve this problem. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density, so as to solve the problem that the existing methods for improving the compaction density of lithium iron manganese phosphate positive electrode materials are relatively complicated and have high implementation costs.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density, comprising the following specific steps:

[0007] S1: weighing lithium source, manganese source, phosphorus source, iron source and carbon source according to the ratio required by the process and mixing them to obtain raw materials, adding grinding balls and anhydrous ethanol in turn according to the ball-to-material ratio, large-small ball ratio and solid-liquid ratio and mixing them evenly;

[0008] S2: After the mixed material obtained in step S1 is evenly divided into two groups, the two groups of mixed materials are subjected to continuous high-speed ball milling for different periods of time. During the ball milling, the operation is suspended at a certain interval and exhaust treatment is performed; after the ball milling is completed, the ball milled material is taken out, and after washing and sieving, two groups of uniformly dispersed slurries are obtained;

[0009] S3 mixes the two groups of slurries evenly, adds pure water according to a certain solid content, and then performs a spray drying process; after the spray drying process is completed, the collected powder is ground and placed in a high-temperature tubular furnace for high-temperature sintering, and then ground after cooling to obtain a lithium iron manganese phosphate positive electrode material.

[0010] Preferably, the ball-to-material ratio, i.e., the mass ratio of grinding balls to raw materials, is (0.5-6):1.

[0011] Preferably, the large and small ball ratio refers to two grinding balls with different diameters, wherein the mass ratio of the grinding balls with large diameter to those with small diameter is 2:3.

[0012] Preferably, the solid-liquid ratio refers to the ratio of raw material to anhydrous ethanol of 1:4 to 4:1.

[0013] Preferably, in step S2, the ball milling time of the two groups of mixed materials is 5 to 12 hours, and the operating speed is 500 to 550 rpm.

[0014] Preferably, the suspension of operation and exhaust treatment in step S2 are specifically as follows: 1 hour before the ball mill operation, pause at the 30th minute and 60th minute respectively to discharge the gas in the ball mill jar; then pause once every 1 hour, discharge the gas in the ball mill jar during each pause, and inject anhydrous ethanol required for ball milling, and continue to run after the exhaust treatment is completed.

[0015] Preferably, in step S3, the two groups of slurries are uniformly mixed by stirring and homogenizing, adding pure water to a solid content of 5 to 30%; and stirring is maintained at a speed of 100 to 200 rpm before spray drying.

[0016] Preferably, in step S3, the rotation speed of the peristaltic pump used for spray drying is 5-20 rpm, the air inlet temperature of the spray dryer is 170-220°C, and the air outlet temperature is 110-130°C.

[0017] Preferably, in step S3, the high temperature sintering process includes: starting from room temperature → heating to 300°C at a rate of 5°C / min in a nitrogen atmosphere, keeping warm for 5 hours → continuing to heat to 650°C at a rate of 5°C / min in a nitrogen atmosphere, keeping warm for 10 hours → naturally cooling to room temperature.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The preparation method of the lithium iron manganese phosphate positive electrode material with a high compaction density realizes the particle size control of the lithium iron manganese phosphate positive electrode material only by ball milling time, and then uniformly mixes materials with different particle sizes to obtain the lithium iron manganese phosphate positive electrode material with a particle size gradient distribution, thereby improving the compaction density of the positive electrode material, and can effectively improve the performance and production efficiency of the lithium iron manganese phosphate positive electrode material.

[0020] 2. The preparation method of the lithium iron manganese phosphate positive electrode material with high compaction density has simple steps and is easy to operate. It does not require special equipment and can be directly implemented on the basis of existing processes. The training of staff is also extremely simple, the cost is low, and it is easy to apply industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope image of the lithium iron manganese phosphate positive electrode material of Example 1 of the present invention.

[0022] Figure 2 This is a scanning electron microscope image of the lithium iron manganese phosphate positive electrode material of Comparative Example 1. DETAILED DESCRIPTION

[0023] The molecular formula of the lithium iron manganese phosphate positive electrode material of the present invention is LiFe x Mn 1-x PO4, wherein x ranges from 0.1 to 0.9. Since the lithium source, manganese source, phosphorus source, iron source and carbon source used in the raw material of the present invention do not improve the existing scheme, the technology known in the art is used, so no special limitation is made. The following provides optional references of the prior art:

[0024] The lithium source used in the preparation method of the lithium ion battery positive electrode material of the present invention includes lithium carbonate, lithium acetate, lithium dihydrogen phosphate, lithium oxalate, etc. The lithium source of the present invention may contain one of these lithium sources or a mixture of more than one of them.

[0025] The method for preparing the lithium iron manganese phosphate positive electrode material of the present invention uses manganese sources including manganese tetraoxide, manganese oxide, manganese trioxide, manganese acetate, manganese oxalate, etc. The manganese source of the present invention may contain one of these manganese sources or a mixture of more than one of them.

[0026] The method for preparing the positive electrode material of lithium ion battery of the present invention adopts phosphorus sources including ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate, phosphoric acid, etc. The phosphorus source of the present invention may contain one of these phosphorus sources or a mixture of more than one of them.

[0027] The method for preparing the positive electrode material of a lithium-ion battery of the present invention uses an iron source including ferric phosphate, ferroferric oxide, ferrous oxide, ferrous acetate, ferrous oxalate, etc. The iron source of the present invention may contain one of these iron sources or a mixture of more than one of them.

[0028] The method for preparing the lithium iron manganese phosphate positive electrode material of the present invention uses carbon sources including inorganic carbon sources such as carbon black, graphene, and graphene oxide, and organic carbon sources such as glucose, sucrose, and citric acid. The carbon source of the present invention may contain one of these carbon sources, or a mixture of more than one of them; the carbon source is added in an amount of 20 to 35% of the total mass of the lithium source, manganese source, phosphorus source, and iron source.

[0029] Example 1

[0030] Weigh 17.76g lithium carbonate, 25.68g manganese tetraoxide, 27.88g ammonium dihydrogen phosphate, 24.12g ferric phosphate, and 19.22g citric acid, add grinding balls and anhydrous ethanol in proportion and mix well. The mass ratio of grinding balls to abrasives is 4:1, the mass ratio of large balls (2mm) to small balls (1mm) is 2:3, and the ratio of anhydrous ethanol to abrasives is 2:3.

[0031] The uniform mixture was divided into two groups and placed in two 250ml zirconia ball mills. The two groups of mixtures were ball milled at a speed of 500r / min using a planetary ball mill for a total of 6h and 10h, respectively. One hour before the ball milling operation, the ball mill was paused at 30min and 60min, the fixed seat was loosened, and the gas in the ball mill was discharged; then the ball mill was paused once every 1h, and the gas in the ball mill was discharged during each pause, and 5ml of anhydrous ethanol was injected. After the ball milling was completed, the mixture in the ball mill was taken out, rinsed with deionized water and sieved to obtain two groups of ball mill materials.

[0032] After the two groups of ball mill materials are prepared, they are evenly mixed, and stirred continuously after homogenization. Pure water is added until the solid content reaches 5%. The slurry is then stirred continuously at a stirring rate of 120r / min, and the spray drying process is carried out at the same time. The parameters of the spray drying process are set as follows: peristaltic pump speed 5rpm, spray dryer inlet temperature 220℃, and outlet temperature 130℃.

[0033] After spray drying is completed, the obtained spray-dried powder is loaded into a sintering boat and placed in a high-temperature tube furnace for high-temperature sintering. The sintering mechanism is: starting from room temperature → heating to 300°C at a rate of 5°C / min under a nitrogen atmosphere (flow rate 300), maintaining for 5 hours → continuing to heat to 650°C at a rate of 5°C / min under a nitrogen atmosphere (flow rate 300), maintaining for 10 hours → naturally cooling to room temperature. After sintering is completed, the obtained sintered powder is poured into a mortar and ground, and finally the lithium iron manganese phosphate positive electrode material is obtained.

[0034] Example 2

[0035] Weigh 14.8g lithium carbonate, 25.68g manganese tetraoxide, 27.88g ammonium dihydrogen phosphate, 24.12g ferric phosphate, and 19.22g citric acid, add grinding balls and anhydrous ethanol in proportion and mix well. The mass ratio of grinding balls to abrasives is 4:1, the mass ratio of large balls (1mm) to small balls (0.6mm) is 2:3, and the ratio of anhydrous ethanol to abrasives is 2:3.

[0036] The uniform mixture was divided into two groups and placed in two 250ml zirconia ball mills. The two groups of mixtures were ball milled at a speed of 550r / min using a planetary ball mill for a total of 5h and 12h, respectively. One hour before the ball milling operation, the ball mill was paused at 30min and 60min, the fixed seat was loosened, and the gas in the ball mill was discharged; then the ball mill was paused once every 1h, and the gas in the ball mill was discharged during each pause, and 5ml of anhydrous ethanol was injected. After the ball milling was completed, the mixture in the ball mill was taken out, rinsed with deionized water and sieved to obtain two groups of ball mill materials.

[0037] After the two groups of ball mill materials are prepared, they are evenly mixed, and stirred continuously after homogenization. Pure water is added until the solid content reaches 20%. The slurry is then stirred continuously at a stirring rate of 200r / min, and the spray drying process is carried out at the same time. The parameters of the spray drying process are set as follows: peristaltic pump speed 20rpm, spray dryer inlet temperature 170℃, and outlet temperature 110℃.

[0038] After spray drying is completed, the obtained spray-dried powder is loaded into a sintering boat and placed in a high-temperature tube furnace for high-temperature sintering. The sintering mechanism is: starting from room temperature → heating to 300°C at a rate of 5°C / min under a nitrogen atmosphere (flow rate 300), maintaining for 5 hours → continuing to heat to 650°C at a rate of 5°C / min under a nitrogen atmosphere (flow rate 300), maintaining for 10 hours → naturally cooling to room temperature. After sintering is completed, the obtained sintered powder is poured into a mortar and ground, and finally the lithium iron manganese phosphate positive electrode material is obtained.

[0039] Comparative Example 1

[0040] 3.7g lithium carbonate, 19.25g manganese tetraoxide, 11.62g ammonium dihydrogen phosphate, 6.03g iron phosphate, and 9.61g citric acid were weighed in sequence and poured into a 250ml zirconium oxide ball mill, and grinding balls and anhydrous ethanol were added in proportion. The addition mechanism of grinding balls and anhydrous ethanol was as follows: the mass ratio of grinding balls to abrasives was 4:1, the mass ratio of large balls (4mm) to small balls (2mm) was 2:3, and the ratio of anhydrous ethanol to abrasives was 1.5:1.

[0041] The mixed material was ball milled at a speed of 500 r / min for a total of 10 hours. During the ball milling operation, the ball mill was paused at 30 minutes and 60 minutes, the fixed base was loosened, and the gas in the ball mill was discharged; then the ball mill was paused every 2 hours, the gas in the ball mill was discharged during each pause, and 5 ml of anhydrous ethanol was injected. After 8 hours of ball milling, the mixture in the ball mill was taken out, rinsed with deionized water and sieved to obtain a uniformly dispersed slurry.

[0042] After the slurry is homogenized, it is continuously stirred and pure water is added until the solid content reaches 5%. The slurry is then continuously stirred at a stirring rate of 120r / min while the spray drying process is performed. The parameters of the spray drying process are set as follows: peristaltic pump speed 5rpm, spray dryer inlet temperature 220℃, and outlet temperature 130℃.

[0043] After spray drying is completed, the obtained spray-dried powder is loaded into a sintering boat and placed in a high-temperature tube furnace for high-temperature sintering. The sintering mechanism is: starting from room temperature → heating to 300°C at a rate of 5°C / min under a nitrogen atmosphere (flow rate 300), maintaining for 5 hours → continuing to heat to 650°C at a rate of 5°C / min under a nitrogen atmosphere (flow rate 300), maintaining for 10 hours → naturally cooling to room temperature. After sintering is completed, the obtained sintered powder is poured into a mortar and ground, and finally the lithium iron manganese phosphate positive electrode material is obtained.

[0044] Comparative Example 2

[0045] Weigh 8.88g lithium carbonate, 12.84g manganese tetraoxide, 13.94g ammonium dihydrogen phosphate, 12.06g iron phosphate, and 9.61g citric acid, mix them, and then add grinding balls and anhydrous ethanol in proportion. The mass ratio of grinding balls to abrasives is 4:1, the mass ratio of large balls (2mm) to small balls (1mm) is 2:3, and the ratio of anhydrous ethanol to abrasives is 2:3.

[0046] The uniform mixture was placed in a 250ml zirconium oxide ball mill and ball milled for 10 hours at a speed of 500r / min using a planetary ball mill. One hour before the ball milling operation, the mixture was paused at 30min and 60min, the fixed seat was loosened, and the gas in the ball mill was discharged; then the mixture was paused every 1h, the gas in the ball mill was discharged during each pause, and 5ml of anhydrous ethanol was injected. After the ball milling was completed, the mixture in the ball mill was taken out, rinsed with deionized water and sieved to obtain the ball mill material.

[0047] Pure water was added to the ball mill until the solid content reached 5%. The slurry was then stirred at a stirring rate of 120 r / min while the spray drying process was carried out. The parameters of the spray drying process were set as follows: peristaltic pump speed 5 rpm, spray dryer inlet temperature 220 ° C, and outlet temperature 130 ° C.

[0048] After spray drying is completed, the obtained spray-dried powder is loaded into a sintering boat and placed in a high-temperature tube furnace for high-temperature sintering. The sintering mechanism is: starting from room temperature → heating to 300°C at a rate of 5°C / min under a nitrogen atmosphere (flow rate 300), maintaining for 5 hours → continuing to heat to 650°C at a rate of 5°C / min under a nitrogen atmosphere (flow rate 300), maintaining for 10 hours → naturally cooling to room temperature. After sintering is completed, the obtained sintered powder is poured into a mortar and ground, and finally the lithium iron manganese phosphate positive electrode material is obtained.

[0049] The powder compaction density of the lithium iron manganese phosphate positive electrode material prepared in the embodiment and the comparative example is shown in Table 1.

[0050] Table 1 Compacted density values ​​of products in embodiments and comparative examples

[0051] sample Example 1 Example 2 Comparative Example 1 Comparative Example 2 <![CDATA[Compaction density (g / cm 3 )]]> 2.439 2.574 2.191 1.874

[0052] The precursor particles of the method of the present invention have a stable and uniform carbon coating effect, and the precursor particles are complete and uniform, without obvious particle breakage; Figure 1 and Figure 2 It can be seen that the present invention achieves close arrangement of particles inside the material by regulating the particle size gradient of the lithium iron manganese phosphate positive electrode material. The obtained positive electrode material has a stable structure, and particles of different particle sizes are evenly arranged in a gradient, thereby improving the compaction density of the product.

[0053] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.

[0054] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density, characterized in that: The specific steps include: S1: weighing lithium source, manganese source, phosphorus source, iron source and carbon source according to the ratio required by the process and mixing them to obtain raw materials, adding grinding balls and anhydrous ethanol in turn according to the ball-to-material ratio, large-small ball ratio and solid-liquid ratio and mixing them evenly; S2: After the mixed material obtained in step S1 is evenly divided into two groups, the two groups of mixed materials are subjected to continuous high-speed ball milling for different periods of time. During the ball milling, the operation is suspended at a certain interval and exhaust treatment is performed; after the ball milling is completed, the ball milled material is taken out, and after washing and sieving, two groups of uniformly dispersed slurries are obtained; S3 mixes the two groups of slurries evenly, adds pure water according to a certain solid content, and then performs a spray drying process; after the spray drying process is completed, the collected powder is ground and placed in a high-temperature tubular furnace for high-temperature sintering, and then ground after cooling to obtain a lithium iron manganese phosphate positive electrode material.

2. The method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: The ball-to-material ratio, i.e., the mass ratio of grinding balls to raw materials, is (0.5-6):

1.

3. The method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: The large and small ball ratio refers to two grinding balls with different diameters, wherein the mass ratio of the grinding balls with large diameter to those with small diameter is 2:

3.

4. The method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: The solid-liquid ratio refers to the ratio of raw material to anhydrous ethanol of 1:4 to 4:

1.

5. The method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In step S2, the ball milling time of the two groups of mixed materials is 5 to 12 hours, and the operating speed is 500 to 550 revolutions per minute.

6. The method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: The suspension operation and exhaust treatment in step S2 are specifically as follows: 1 hour before the ball mill operation, the operation is suspended at the 30th minute and the 60th minute, respectively, to exhaust the gas in the ball mill jar; then the operation is suspended once every 1 hour, the gas in the ball mill jar is exhausted during each suspension, and the anhydrous ethanol required for the ball mill is injected, and the operation is continued after the exhaust treatment is completed.

7. The method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In step S3, the two groups of slurries are uniformly mixed in a manner including stirring and homogenizing, adding pure water to a solid content of 5 to 30%; and maintaining stirring at a rotation speed of 100 to 200 rpm before spray drying.

8. The method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In step S3, the rotation speed of the peristaltic pump used for spray drying is 5-20 rpm, the air inlet temperature of the spray dryer is 170-220° C., and the air outlet temperature is 110-130° C.

9. The method for preparing a lithium iron manganese phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In step S3, the high temperature sintering process includes: starting from room temperature → heating to 300°C at a rate of 5°C / min in a nitrogen atmosphere, keeping warm for 5 hours → continuing to heat to 650°C at a rate of 5°C / min in a nitrogen atmosphere, keeping warm for 10 hours → naturally cooling to room temperature.

Citation Information

Patent Citations

  • Preparation method of high-compaction-density lithium manganese iron phosphate

    CN116986574A

Cited By

  • Preparation method of lithium ion battery manganese positive electrode material

    CN121493917A